MSME Sustainability as the Key to Sustainability: Role and Contribution of MSMEs to Sustainability with a Bibliometric Approach and Literature Review - Gunawan, William Ben (Universitas Tanjungpura, 2025)
This study explores the contribution of micro, small, and medium enterprises (MSMEs) to sustainability through bibliometric analysis and a literature review, focusing on their role in supporting economic, environmental, and social sustainability in Indonesia. A bibliometric approach was employed to evaluate research trends, publication patterns, and the distribution of studies by country in literature published between 2019 and 2024. Literature searches were conducted in the Scopus database using the keywords